Polyimide varnish with excellent voltage endurance characteristics, and polyimide coating material prepared therefrom

JP2025033000AActive Publication Date: 2025-03-12PI ADVANCED MATERIALS CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2024144334
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-08-28
Filing Date
2024-08-26
Publication Date
2025-03-12
Estimated Expiration
2044-08-26

AI Technical Summary

Benefits of technology

【0056】 本発明のポリイミドワニスは、所定の範囲の水分含有量を有するナノシリカを所定の範囲で含むことにより、電圧耐久特性に優れ、且つヘイズのような物性にも優れる効果がある。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025033000000001
    Figure 2025033000000001
  • Figure 2025033000000002
    Figure 2025033000000002
  • Figure 2025033000000003
    Figure 2025033000000003
Patent Text Reader

Abstract

To provide a polyimide varnish with excellent voltage endurance characteristics, and a polyimide coating material prepared therefrom.SOLUTION: Provided is a polyimide varnish comprising polyamic acid and nanosilica, where the content of the nanosilica is 5-23 wt.% based on the solid content of the polyamic acid, and where the nanosilica has a moisture content of less than 0.5 wt.%.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a polyimide varnish and a polyimide coating produced therewith, and more particularly to a polyimide varnish having excellent voltage endurance characteristics and a polyimide coating produced therewith. [Background technology]

[0002] Generally, polyimide (PI) resin is a highly heat-resistant resin produced by solution polymerization of aromatic dianhydride and aromatic diamine or aromatic diisocyanate to produce a polyamic acid derivative, followed by ring-closing dehydration at high temperature and imidization. Polyimide resin is an insoluble, infusible, ultra-high heat-resistant resin with excellent properties such as thermal oxidation resistance, heat resistance, radiation resistance, low temperature properties, and chemical resistance. It is used in a wide range of fields in advanced heat-resistant materials such as automotive materials, aviation materials, and space ray materials, as well as in electronic materials such as insulating coating agents, insulating films, semiconductors, and electrode protection films for TFT-LCDs. Recently, it has also been used in display materials such as optical fibers and liquid crystal alignment films, and in transparent electrode films, either by containing conductive fillers in the film or coating the surface.

[0003] In particular, insulated wires used as coil windings for motors and other devices, the insulating layer (insulating coating) that covers the conductor is required to have excellent insulation properties, adhesion to the conductor, heat resistance, mechanical strength, etc., and polyimide is used as the resin that forms the insulating layer.

[0004] However, in electrical equipment that requires high applicable voltages, such as motors operated at high voltages, high voltages are applied to the insulated wires that make up the electrical equipment, and there is still a need to develop polyimides with excellent voltage durability that can withstand such high voltages.

[0005] Specifically, partial discharge (corona discharge) is likely to occur on the surface of the coating to which a high voltage is applied, and if the occurrence of corona discharge causes a local temperature rise or the generation of ozone or ions, the coating of the insulated electric wire will deteriorate, causing early dielectric breakdown and shortening the life of the electrical equipment. Therefore, in order to use polyimide as a coating material for a conductor, particularly as a coating to which a high voltage is applied, it is necessary to improve voltage endurance properties such as dielectric breakdown voltage performance and corona discharge inception voltage. Summary of the Invention [Problem to be solved by the invention]

[0006] The present invention provides a polyimide varnish that is excellent in physical properties such as voltage endurance characteristics and haze by containing nanosilica having a moisture content within a specified range.

[0007] The present invention also provides a polyimide cured product obtained by curing the polyimide varnish.

[0008] The present invention also provides a polyimide coating comprising the polyimide varnish. [Means for solving the problem]

[0009] Since the present invention can be modified in various ways and can have various embodiments, a specific embodiment will be illustrated and described in detail. However, it should be understood that the present invention is not limited to the specific embodiment, and includes all modifications, equivalents, or alternatives included in the spirit and technical scope of the present invention.

[0010] The terms used in this application are merely used to describe certain embodiments and are not intended to limit the present invention. A singular expression includes a plural expression unless the context clearly indicates otherwise. In this application, the terms "include" or "have" are used to specify the presence of a feature, number, step, operation, component, part, or combination thereof described in the specification, and should be understood not to preclude the presence or additional possibility of one or more other features, numbers, steps, operations, components, parts, or combinations thereof.

[0011] Whenever an amount, concentration, or other value or parameter is given herein by a range, a preferred range or a recitation of an upper preferred value and a lower preferred value, that is to be understood as specifically disclosing all ranges formed by any pair of any upper range limit or preferred value and any lower range limit or preferred value, regardless of whether a range is otherwise disclosed.

[0012] Where a range of numerical values ​​is recited herein, unless otherwise stated, it is intended that the endpoints of the range and the scope of the invention within that range are not limited to the specific values ​​recited when defining the range.

[0013] As used herein, "dianhydrides" is intended to include precursors or derivatives thereof, but may also be referred to as "dianhydride acids," "dianhydrides," or "acid dianhydrides." Although these may not technically be dianhydrides, they nevertheless react with diamines to form polyamic acids, which in turn can be converted to polyimides.

[0014] As used herein, "diamine" is intended to include precursors or derivatives thereof which may not technically be diamines, but which nevertheless react with dianhydride acids to form polyamic acids, which in turn can be converted to polyimides.

[0015] Unless otherwise defined, all terms used herein, including technical or scientific terms, have the same meaning as commonly understood by a person of ordinary skill in the art to which the present invention belongs. Terms such as those defined in commonly used dictionaries should be interpreted as having a meaning consistent with the meaning they have in the context of the relevant art, and should not be interpreted in an ideal or overly formal sense unless expressly defined in this application. Specific contents for implementing the above invention are described as follows.

[0016] Polyimide Varnish The present invention relates to a polyimide varnish which has improved voltage endurance characteristics and can be used for conductor coating.

[0017] In one aspect of the present invention, there is provided a polyimide varnish comprising polyamic acid and nanosilica, wherein the nanosilica comprises 5 to 23% by weight relative to the solid content of the polyamic acid, and the nanosilica has a water content of less than 0.5% by weight.

[0018] Nano Silica The polyimide varnish of the present invention may contain nanosilica, which is nano-sized silicon dioxide (SiO2) fine particles having an average particle size of 1000 nm or less, in order to improve physical properties such as voltage endurance characteristics, and the form and shape of the nanosilica are not particularly limited.

[0019] The nanosilica may be contained in an amount of 5 to 23% by weight based on the solid content of the polyamic acid. For example, the lower limit of the content of the nanosilica may be 5.5% by weight, 6.0% by weight, 6.5% by weight, 7.0% by weight, 8.0% by weight, 9.0% by weight, 10.0% by weight, or 11.0% by weight. The upper limit of the content of the nanosilica may be 22.0% by weight, 21.5% by weight, 21.0% by weight, 20.5% by weight, 20.0% by weight, 19.0% by weight, 18.5% by weight, 18.0% by weight, 17.0% by weight, 16.0% by weight, 15.0% by weight, 14.0% by weight, 13.5% by weight, or 13.0% by weight. If the content of the nanosilica is less than 5% by weight, it is not effective in improving the voltage endurance characteristics, and if it exceeds 23% by weight, it is not preferable because the physical properties may deteriorate. Here, the solid content of the polyamic acid is the total amount of the dianhydride monomer and the diamine monomer used in the polymerization reaction.

[0020] In addition, the nanosilica may have a water content of less than 0.5 wt%. For example, the upper limit of the water content of the nanosilica may be 0.49 wt%, 0.48 wt%, 0.47 wt%, 0.46 wt%, 0.45 wt%, 0.44 wt%, 0.43 wt%, or 0.42 wt% or less. In addition, the lower limit of the water content of the nanosilica is not particularly limited, but may be more than 0 wt%, 0.01 wt%, 0.05 wt%, 0.10 wt%, or 0.15 wt% or more. In addition, if the water content of the nanosilica is 0.5 wt% or more, it is not preferable because it may affect the formation of the molecular weight of the polymer and cause a decrease in physical properties. The nanosilica may be a dispersion in which the nanosilica is dispersed in an organic solvent, and the water content means the water content in the dispersion in which the nanosilica is dispersed.

[0021] The water content of the nanosilica can be measured by the Karl Fischer method, which quantitatively determines the water content in a KS M 0034 sample by reacting it with iodine and sulfur dioxide.

[0022] The nanosilica may have an average particle size of 1 to 200 nm, specifically, for example, 5 to 150 nm, 5 to 100 nm, 5 to 70 nm, 10 to 50 nm, or 10 to 30 nm. The average particle size may be measured by equipment such as BET, SEM, or zeta potential.

[0023] The nanosilica may also be nanosilica surface-modified with an organosilane.

[0024] In addition, the organic silane of the nanosilica surface-modified with an organic silane is methyltrimethoxysilane, hexamethyldisiloxane, n-octyltrimethoxysilane, n-octyltriethoxysilane, isooctyltrimethoxysilane, dodecyltrimethoxysilane, octadecyltrimethoxysilane, propyltrimethoxysilane, hexyltrimethoxysilane, 3-methacryloxypropyltrimethoxysilane, 3-acryloxypropyltrimethoxysilane, 3-(methacryloxy)propyltriethoxysilane, 3-(methacryloxy)propylmethyldimethoxysilane, 3-(acryloxypropyl)methyldimethoxysilane, 3-(methacryloxy)propyl ... Propyldimethylethoxysilane, styrylethyltrimethoxysilane, phenyltriethoxysilane, p-tolyltriethoxysilane, vinylmethyldiacetoxysilane, vinyldimethylethoxysilane, vinylmethyldiethoxysilane, vinyltrimethoxysilane, vinyltriethoxysilane, vinyltriacetoxysilane, vinyltriisopropoxysilane, vinyltriphenoxysilane, vinyltri-t-butoxysilane, vinyltris(isobutoxy)silane, vinyltriisopropenoxysilane, vinyltris(2-methoxyethoxy)silane, diisopropylethylamine phenyltrimethoxysilane (N,N-Diisopropylethylamine The silane may include one or more selected from the group consisting of N-phenyl-3-aminopropyltrimethoxysilane (PAPTES), N-phenyl-3-aminopropyltrimethoxysilane (PPTMS ...

[0025] In addition, the nanosilica surface-modified with the organic silane may have a compound containing at least one phenyl group at the end of the surface of the nanosilica and a compound containing at least one amine group, hydroxyl group, thiol group, or epoxide group at the end bonded thereto. Specifically, the compound containing at least one phenyl group at the end may be phenyltrimethoxysilane (PTMS) or phenylaminopropyltrimethoxysilane (PAPTES). In addition, the compound containing at least one amine group, hydroxyl group, thiol group, or epoxide group at the end may be glycidoxypropyltrimethoxysilane (GPTMS) or aminopropyltrimethoxysilane (APTMS).

[0026] The nanosilica surface-modified with the organic silane can be produced by subjecting nanosilica to a surface treatment with the organic silane. For example, the organic silane is heated under acidic or basic conditions, and surface treatment is performed for about 1 to 24 hours to obtain nanosilica. Surface modification can also be achieved by other known methods, for example, by mixing the organic silane with a solvent and then reacting at a temperature of 10 to 100°C or 20 to 60°C for 1 to 10 hours or 1 to 5 hours to obtain surface-modified nanosilica. In order to bond two or more compounds to the surface of nanosilica, each of the above methods can be performed.

[0027] The nanosilica surface-modified with the organic silane of the present invention prevents the aggregation of inorganic particles in the polyimide varnish, and the functional groups of the compound enhance the interaction with the solid content (polyamic acid), thereby improving dispersibility and miscibility.

[0028] Polyamic Acid In the present invention, the polyamic acid may contain a dianhydride monomer and a diamine monomer as polymerized units.

[0029] The dianhydride monomers include pyromellitic dianhydride (PMDA), biphenyl tetracarboxylic dianhydride (BPDA), benzophenone tetracarboxylic dianhydride (BTDA), oxydiphthalic dianhydride (ODPA), diphenylsulfone-3,4,3',4'-tetracarboxylic dianhydride (DSDA), bis(3,4-dicarboxyphenyl)sulfide dianhydride, 2,2-bis(3,4-dicarboxyphenyl)-1,1,1,3,3,3-hexafluoropropane dianhydride, 2,3,3',4'-benzophenone tetracarboxylic dianhydride, bis(3,4-dicarboxyphenyl)methane dianhydride, 2,2-bis(3,4-dicarboxyphenyl)propane dianhydride, p-phenylene bis(trimeric monoester acid anhydride), p-biphenyl The compound may include one or more selected from the group consisting of nylene bis(trimeristic monoester acid anhydride), m-terphenyl-3,4,3',4'-tetracarboxylic dianhydride, p-terphenyl-3,4,3',4'-tetracarboxylic dianhydride, 1,3-bis(3,4-dicarboxyphenoxy)benzene dianhydride, 1,4-bis(3,4-dicarboxyphenoxy)benzene dianhydride, 1,4-bis(3,4-dicarboxyphenoxy)biphenyl dianhydride, 2,2-bis[(3,4-dicarboxyphenoxy)phenyl]propane dianhydride (BPADA), 2,3,6,7-naphthalene tetracarboxylic dianhydride, 1,4,5,8-naphthalene tetracarboxylic dianhydride, and 4,4'-(2,2-hexafluoroisopropylidene)diphthalic dianhydride.

[0030] Specifically, the dianhydride monomer may include one or more selected from the group consisting of pyromellitic dianhydride (PMDA), biphenyltetracarboxylic dianhydride (BPDA) and benzophenonetetracarboxylic dianhydride (BTDA), and may preferably include pyromellitic dianhydride (PMDA).

[0031] In addition, the diamine monomer may be 1,4-diaminobenzene (PPD), 4,4'-diaminodiphenyl ether (ODA), 2,2-bisaminophenoxyphenylpropane (BAPP), metaphenylenediamine, 3,3'-dimethylbenzidine, 2,2'-dimethylbenzidine, 2,4-diaminotoluene, 2,6-diaminotoluene, 3,5-diaminobenzoic acid (DABA), 3,3'-dimethyl-4,4'-diaminobiphenyl, 2,2'-dimethyl-4,4'-diaminobiphenyl (m-tolidine), 2,2'-bis(trifluoromethyl)phenylpropane (TFA ... 3,3'-Dimethyl-4,4'-diaminobiphenyl, 3,3'-Dimethyl-4,4'-diaminodiphenylmethane, 3,3'-Dicarboxy-4,4'-diaminodiphenylmethane, 3,3',5,5'-Tetramethyl-4,4'-diaminodiphenylmethane, 4,4'-diaminobenzanilide, 3,3'-Dimethoxybenzidine, 2,2'-Dimethoxybenzidine, 3,3'-Diaminodiphenyl ether, 3,4'-Diaminodiphenyl ether, 3,3'-Diaminodiphenyl sulfide, 3,4'-Diaminodiphenyl sulfide, 4,4'-Diamino Aminodiphenyl sulfide, 3,3'-diaminodiphenyl sulfone, 3,4'-diaminodiphenyl sulfone, 4,4'-diaminodiphenyl sulfone, 3,3'-diaminobenzophenone, 4,4'-diaminobenzophenone, 3,3'-diamino-4,4'-dichlorobenzophenone, 3,3'-diamino-4,4'-dimethoxybenzophenone, 3,3'-diaminodiphenylmethane, 3,4'-diaminodiphenylmethane, 4,4'-diaminodiphenylmethane, 2,2-bis(3-aminophenyl)propane, 2,2-bis(4-aminophenyl)propane nophenyl)propane, 2,2-bis(3-aminophenyl)-1,1,1,3,3,3-hexafluoropropane, 2,2-bis(4-aminophenyl)-1,1,1,3,3,3-hexafluoropropane, 3,3'-diaminodiphenyl sulfoxide, 3,4'-diaminodiphenyl sulfoxide, 4,4'-diaminodiphenyl sulfoxide, 1,3-bis(3-aminophenyl)benzene, 1,3-bis(4-aminophenyl)benzene, 1,4-bis(3-aminophenyl)benzene, 1,4-bis(4-aminophenyl)benzene, 1,3-bis(4-aminophenoxy)benzene (TPE-R), 1,4-bis(3-aminophenoxy)benzene (TPE-Q), 1,3-bis(3-aminophenoxy)-4-trifluoromethylbenzene, 3,3'-diamino-4-(4-phenyl)phenoxybenzophenone, 3,3'-diamino-4,4'-di(4-phenylphenoxy)benzophenone, 1,3-bis(3-aminophenylsulfide)benzene, 1,3-bis(4-aminophenylsulfide)benzene, 1,4-bis(4-aminophenylsulfide)benzene, 1,3 -Bis(3-aminophenylsulfone)benzene, 1,3-bis(4-aminophenylsulfone)benzene, 1,4-bis(4-aminophenylsulfone)benzene, 1,3-bis[2-(4-aminophenyl)isopropyl]benzene, 1,4-bis[2-(3-aminophenyl)isopropyl]benzene, 1,4-bis[2-(4-aminophenyl)isopropyl]benzene, 3,3'-bis(3-aminophenoxy)biphenyl, 3,3'-bis(4-aminophenoxy)biphenyl, 4,4'-bis(3-aminophenoxy)biphenyl, 4,4'-bis(4-aminophenoxy)biphenyl, bis[3-(3-aminophenoxy)phenyl]ether, bis[3-(4-aminophenoxy)phenyl]ether, bis[4-(3-aminophenoxy)phenyl]ether, bis[4-(4-aminophenoxy)phenyl]ether, bis[3-(3-aminophenoxy)phenyl]ketone, bis[3-(4-aminophenoxy)phenyl]ketone, bis[4-(3-aminophenoxy)phenyl]ketone, bis[4-(4-amino phenoxy)phenyl]ketone, bis[3-(3-aminophenoxy)phenyl]sulfide, bis[3-(4-aminophenoxy)phenyl]sulfide, bis[4-(3-aminophenoxy)phenyl]sulfide, bis[4-(4-aminophenoxy)phenyl]sulfide, bis[3-(3-aminophenoxy)phenyl]sulfone, bis[3-(4-aminophenoxy)phenyl]sulfone, bis[4-(3-aminophenoxy)phenyl]sulfone, bis[4-(4-aminophen 2,2-bis[3-(3-aminophenoxy)phenyl]propane, 2,2-bis[3-(4-aminophenoxy)phenyl]propane, 2,2-bis[4-(3-aminophenoxy)phenyl]propane, 2,2-bis[3-( The fluorocarbon polymer may include one or more selected from the group consisting of 2,2-bis[3-(4-aminophenoxy)phenyl]-1,1,1,3,3,3-hexafluoropropane, 2,2-bis[4-(3-aminophenoxy)phenyl]-1,1,1,3,3,3-hexafluoropropane, and 2,2-bis[4-(4-aminophenoxy)phenyl]-1,1,1,3,3,3-hexafluoropropane.

[0032] Specifically, the diamine monomer may include one or more selected from the group consisting of 1,4-diaminobenzene (PPD), 4,4'-diaminodiphenyl ether (ODA), 2,2-bisaminophenoxyphenylpropane (BAPP) and 1,3-bis(4-aminophenoxy)benzene (TPE-R), and preferably includes 4,4'-diaminodiphenyl ether (ODA).

[0033] The polyamic acid can contain pyromellitic dianhydride (PMDA) and 4,4'-diaminodiphenyl ether (ODA) as polymerized units.

[0034] In the present invention, pyromellitic dianhydride (PMDA) may be contained in a ratio of 50 mol% or more of the total dianhydride monomers, specifically, 60 mol% or more, 70 mol% or more, 75 mol% or more, 80 mol% or more, 85 mol% or more, 90 mol% or more, 95 mol% or more, 99 mol% or more, or 100 mol% or more.

[0035] In addition, 4,4'-diaminodiphenyl ether (ODA) may be contained in a ratio of 50 mol% or more of the total diamine monomers, specifically, 60 mol% or more, 70 mol% or more, 75 mol% or more, 80 mol% or more, 85 mol% or more, 90 mol% or more, 95 mol% or more, 99 mol% or more, or 100 mol% or more.

[0036] In the polyamic acid of the present invention, the dianhydride monomer may be 95 to 105 mol% relative to 100 mol% of the diamine monomer, and for example, the lower limit may be 96 mol% or more, 97 mol% or more, 98 mol% or more, 99 mol% or more, or 99.5 mol% or more, and the upper limit may be 104 mol% or less, 103 mol% or less, 102 mol% or less, 101 mol% or less, or 100.5 mol% or less. In one embodiment, the diamine monomer and the dianhydride monomer may react in substantially equimolar amounts.

[0037] The molar ratio of the dianhydride monomer to the diamine monomer may be 6:4 to 4:6, preferably 5.5:4.5 to 4.5:6.5, and more preferably 5:5.

[0038] The solid content of the polyamic acid may be 10 to 50% by weight. The lower limit of the solid content may be, for example, 13% by weight or more, 15% by weight or more, 18% by weight or more, 20% by weight or more, 23% by weight or more, or 24% by weight or more, and the upper limit may be, for example, 48% by weight or less, 45% by weight or less, 43% by weight or less, 40% by weight or less, 38% by weight or less, 35% by weight or less, 33% by weight or less, 30% by weight or less, or 27% by weight or less. By adjusting the solid content of the polyamic acid, it is possible to control the increase in viscosity and shorten the process time during the curing process.

[0039] Organic solvents In the present invention, the polyimide varnish further includes an organic solvent, and the organic solvent is not particularly limited as long as it is an organic solvent in which polyamic acid can be dissolved. As an example, the organic solvent may be an aprotic polar solvent.

[0040] Specifically, the organic solvent may include one or more selected from the group consisting of N-methyl-pyrrolidone (NMP), N,N'-dimethylformamide (DMF), N,N'-diethylformamide (DEF), N,N'-dimethylacetamide (DMAc), dimethylpropanamide (DMPA), N,N-diethylacetamide (DEAc), dimethylsulfoxide (DMSO), 3-methoxy-N,N-dimethylpropanamide (KJCMPA), p-chlorophenol, o-chlorophenol, γ-butyrolactone (GBL), diglyme, and naphthalene. Preferably, N-methyl-pyrrolidone (NMP), N,N'-dimethylformamide (DMF), N,N'-dimethylacetamide (DMAc), dimethylsulfoxide (DMSO), etc. may be used.

[0041] In addition, the organic solvent may further include a modifier containing a hydroxyl group (OH) or an amine group (NH), and examples of the modifier containing a hydroxyl group (OH) or an amine group (NH) include ethylamine, triethanolamine, dimethylamine, trimethylamine, diethylenetriamine, ethylenediamine, tributylamine, pyridine, pyrrolidine, methanol, ethanol, propanol, isopropanol, sec-butanol, tert-butanol, n-amyl alcohol, isoamyl alcohol, hexanol, octanol, capryl alcohol, nonyl alcohol, decyl alcohol, undecyl alcohol, lauryl alcohol, myristyl alcohol, cetyl alcohol, stearyl alcohol, allyl alcohol, crotyl alcohol, propargyl alcohol, ethylene glycol, propylene glycol, benzyl alcohol, and phenol. The modifier may react with the dianhydride monomer to control the reactivity.

[0042] Polyimide Varnish The polyimide varnish is heated at 30° C. for 1 s. -1 The viscosity measured under the condition of a shear rate of 1 / s may be in the range of 500 to 20,000 cP. For example, the upper limit may be 20,000 cP, 15,000 cP, or 10,000 cP or less. The lower limit is not particularly limited, but may be 1,000 cP, 1,200 cP, 1,500 cP, or 1,800 cP or more. In one embodiment, the viscosity may be measured using a Rheostress 600 manufactured by Haake Co., Ltd., and may be measured under the conditions of a shear rate of 1 / s, a temperature of 30°C, and a plate gap of 1 mm. The present invention can provide a polyimide varnish having excellent processability by adjusting the viscosity range.

[0043] The polyimide varnish may have a haze of 1.5% or less. For example, the upper limit of the haze may be 1.4% or less, 1.3% or less, 1.2% or less, 1.1% or less, 1% or less, 0.9% or less, or 0.8% or less, and the lower limit may be, but is not limited to, more than 0%, 0.05% or more, or 0.1% or more. In one embodiment, the haze is measured in accordance with ASTM E308 using equipment manufactured by HunterLab.

[0044] Polyimide varnish cured products and coatings In another aspect of the present invention, a cured polyimide product is provided by curing the polyimide varnish. The cured polyimide product may include a polyimide cured product in the form of a film or a polyimide coating.

[0045] The polyimide cured material may have a haze of 1.5% or less. For example, the upper limit of the haze may be 1.4% or less, 1.3% or less, 1.2% or less, 1.1% or less, 1% or less, 0.9% or less, 0.8% or less, 0.7% or less, 0.6% or less, or 0.5% or less, and the lower limit may be, but is not limited to, more than 0%, 0.05% or more, or 0.1% or more. In one embodiment, the haze is measured using equipment manufactured by HunterLab in accordance with ASTM E308, and the thickness of the polyimide cured material is 20±1.0 μm.

[0046] The polyimide cured product may have a voltage endurance characteristic, which is the time that an insulating material can withstand a predetermined voltage according to IEC-60851-5, of 300 minutes or more, and the lower limit of the voltage endurance characteristic may be, for example, 400 minutes or more, 500 minutes or more, 550 minutes or more, 600 minutes or more, 650 minutes or more, 700 minutes or more, 750 minutes or more, 800 minutes or more, 850 minutes or more, 900 minutes or more, 950 minutes or more, 970 minutes or more, 980 minutes or more, 1000 minutes or more, 1100 minutes or more, 1200 minutes or more, 1300 minutes or more, 1400 minutes or more, 1500 minutes or more, or 2000 minutes or more. The upper limit is not particularly limited, but may be 4,000 minutes or less. The voltage durability characteristic was measured by connecting the polyimide coating to a jig, applying a voltage of AC 1.5 kV (frequency 60 Hz), and measuring the time until a leakage current of 5 mA or more was detected. Here, the thickness of the polyimide cured material may be 26±1.0 μm.

[0047] In addition, the present invention can improve voltage endurance characteristics by including nano-silica having a moisture content within a predetermined range at a high content within a predetermined range.

[0048] In another aspect of the present invention, there is provided a polyimide coating comprising the above-mentioned cured polyimide.

[0049] In one embodiment, a method for producing the polyimide coating may include the steps of coating a surface of a conductor with a polyimide varnish and imidizing the polyimide varnish coated on the surface of the conductor.

[0050] The conductor may be a copper wire made of copper or a copper alloy, but may also be a conductor made of other metal materials such as silver spring, or various metal-plated wires such as aluminum or tin-plated wire. The thickness of the conductor and the coating may conform to KS C 3107. The diameter of the conductor may be within a range of 0.3 to 3.2 mm, and the standard coating thickness of the coating (average value of the maximum coating thickness and the minimum coating thickness) may be 21 to 194 μm for type 0, 14 to 169 μm for type 1, and 10 to 31 μm for type 2. The cross-sectional shape of the conductor may be, but is not limited to, a ring wire, a rectangular wire, a hexagonal wire, or the like.

[0051] In another aspect of the present invention, there is provided an electric wire comprising the polyimide coating.

[0052] Specifically, the coated electric wire may include a polyimide coating produced by coating the surface of an electric wire with the polyimide varnish and imidizing the polyimide varnish. In one specific example, the coated electric wire may include an electric wire and a coating formed by coating the surface of the electric wire with the polyimide and imidizing the polyimide.

[0053] The present invention also provides an electronic device including the coated electric wire, for example, an electric motor.

[0054] In another aspect of the present invention, a part is provided that includes a molded body formed from a polyimide varnish.

[0055] Specifically, the parts can be electronic circuit board parts, semiconductor devices, lithium ion battery parts, solar cell parts, fuel cell parts, motor windings, engine peripheral parts, paints, optical parts, heat dissipation materials, electromagnetic wave shielding materials, surge parts, dental materials, slide coatings, and electrostatic chucks. Effect of the Invention

[0056] The polyimide varnish of the present invention contains nanosilica having a moisture content within a specified range, and thus has the effect of exhibiting excellent voltage durability characteristics and excellent physical properties such as haze.

[0057] In addition, the present invention has an effect of being highly applicable as a conductor coating for use in windings for electric vehicles (EVs). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0058] In order to facilitate understanding of the present invention, examples are presented. The following examples are provided to facilitate understanding of the present invention, and are not intended to limit the scope of the present invention.

[0059] <Example> Production Example 1. Nanosilica surface-treated with organic silane Nanosilica 1 (dimethylacetamide dispersed silica sol, silica solid concentration 30 wt%, average silica particle size 10-30 nm, water content 0.4 wt%) was prepared, which was surface-treated with organic silane. Here, the water content is the weight percent relative to the total mass of the nanosilica dispersion, and the water content of the nanosilica was measured by the Karl Fischer method. Specifically, the water content was measured by quantitatively reacting the water in the KS M 0034 sample with iodine and sulfur dioxide.

[0060] Comparative Production Example 1. Nanosilica Nanosilica (silica sol dispersed in N-methylpyrrolidone, silica solid concentration 30 wt%, average silica particle size 10-20 nm, water content 0.8 wt%) was prepared. Here, the water content is the weight percent relative to the total mass of the nanosilica dispersion, and the water content of the nanosilica was measured by the Karl Fischer method. Specifically, the water content was measured by using the quantitative reaction of the water in the KS M 0034 sample with iodine and sulfur dioxide.

[0061] Example 1. Polyimide varnish Example 1-1 An organic solvent containing dimethylacetamide (DMAc) and a modifier (0-2 mol%) was added to a reaction vessel replaced with nitrogen gas, and nanosilica surface-treated with an organic silane according to Preparation Example 1 (6 wt% based on polyimide solid content) and pyromellitic dianhydride (PMDA) (92 mol%) as a dianhydride monomer were mixed and stirred at 40°C for 30 minutes. Next, 4,4'-diaminodiphenyl ether (ODA) (100 mol%) and pyromellitic dianhydride (PMDA) (8 mol%) were added as diamine monomers, and the mixture was stirred and polymerized at 40°C for about 1 hour to produce a polyimide varnish (polyimide solid content 25 wt%).

[0062] Examples 1-2 to 1-7 As shown in Table 1 below, polyimide varnishes were prepared in the same manner as in Example 1-1, except that the nanosilica surface-treated with organosilane according to Preparation Example 1 was used in different amounts.

[0063] Comparative Examples 1-1 to 1-2 A polyimide varnish was prepared in the same manner as in Example 1-1, except that instead of using the nanosilica surface-treated with organosilane according to Preparation Example 1, the nanosilica according to Preparation Comparative Example 1 was used at different contents as shown in Table 1 below.

[0064] Comparative Examples 1-3 to 1-4 As shown in Table 1 below, polyimide varnishes were prepared in the same manner as in Example 1-1, except that the nanosilica surface-treated with organosilane according to Preparation Example 1 was used in different amounts.

[0065] Table 1 below shows the composition, solid content, and type and content of nanosilica of the polyamic acid of Examples 1-1 to 1-7 and Comparative Examples 1-1 to 1-4.

[0066] [Table 1]

[0067] Example 2. Polyimide cured product (polyimide film) Example 2-1 The polyimide varnish prepared in Example 1-1 was rotated at a high speed of 2,000 rpm to remove air bubbles, and then the degassed polyimide varnish was applied onto a glass substrate (230 mm×230 mm, thickness: 0.55 mm) using a spin coater.

[0068] The mixture was then cured under a nitrogen atmosphere at 110°C (20 min) → 150°C (20 min) → 200°C (20 min) → 300°C (20 min) to obtain a polyimide cured film (thickness 20±1.0 μm or 26±1.0 μm).

[0069] Examples 2-2 to 2-7 A cured polyimide material was prepared in the same manner as in Example 2-1, except that the polyimide varnish of Examples 1-2 to 1-7 was used instead of the polyimide varnish of Example 1-1.

[0070] Comparative Examples 2-1 to 2-4 A cured polyimide material was prepared in the same manner as in Example 2-1, except that the polyimide varnishes of Comparative Examples 1-1 to 1-4 were used instead of the polyimide varnish of Example 1-1.

[0071] Example 3. Polyimide coating Example 3-1 In a coating and curing oven, the polyimide varnish according to Example 1-1 was applied to a rectangular copper wire 20 to 28 times, and the process of drying and curing was repeated to manufacture an electric wire having a polyimide coating with a coating thickness of 110±10 μm.

[0072] Examples 3-2 to 3-7 An electric wire including a polyimide coating was manufactured in the same manner as in Example 3-1, except that the polyimide varnish according to Examples 1-2 to 1-7 was used instead of the polyimide varnish according to Example 1-1 in Example 3-1.

[0073] <Experimental Example> Experimental Example 1. Evaluation of the physical properties of polyimide (1) Voltage endurance characteristics The polyimide cured film (thickness 26±1.0 μm) of each of the Examples and Comparative Examples was connected to a jig, and a voltage of 1.5 kV AC (frequency 60 Hz) was applied to measure the time until a leak current of 5 mA or more was detected, thereby measuring the voltage durability characteristics according to IEC-60851-5. The results are shown in Table 2 below.

[0074] (2) Haze The haze of the polyimide varnish or the polyimide cured product in the form of a film (thickness: 20±1.0 μm) of the Examples and Comparative Examples was measured in accordance with ASTM E308 using equipment manufactured by HunterLab, and the results are shown in Tables 2 and 3 below.

[0075] [Table 2]

[0076] [Table 3]

[0077] From Table 3, it can be seen that by using nanosilica with a moisture content of less than 0.5 wt%, the polyimide film of the present invention has significantly better voltage endurance characteristics than Comparative Examples 2-1 and 2-2. Also, it can be seen that Examples 2-1 to 2-7 have significantly improved voltage endurance characteristics by containing 6 to 20 wt% nanosilica relative to the polyimide solid content, but Comparative Example 2-3, which falls outside the above content range, has a very low voltage endurance characteristic of less than 300 minutes, and Comparative Example 2-4 was not formed into a film and was unmeasurable.

[0078] Also, according to Tables 3 and 4, the polyimide varnish of the present invention and its cured film form were both able to achieve low levels of haze properties. Specifically, in the case of the varnishes of Examples 1-1 to 1-7, the haze was confirmed to be 0.7% or less, and in the case of the films of Examples 2-1 to 2-7, the haze was confirmed to be 0.8% or less. This means that the nanosilica does not aggregate and is uniformly dispersed.

[0079] Therefore, the present invention provides a polyimide varnish having excellent physical properties such as haze by containing nanosilica having a moisture content within a predetermined range at a high content within a predetermined range, and by using the polyimide varnish, it is possible to provide a polyimide cured product having excellent physical properties such as haze, while realizing excellent voltage endurance characteristics.

[0080] This specification omits detailed descriptions of contents that can be fully recognized and inferred by a person having ordinary skill in the technical field of the present invention, and various modifications are possible within the scope of the technical idea and essential configuration of the present invention other than the specific examples described in this specification. Therefore, the present invention can be implemented in a manner different from that specifically described and exemplified in this specification, and this is something that can be understood by a person having ordinary skill in the technical field of the present invention.

Claims

1. A polyimide varnish comprising a polyamic acid and nanosilica, The nanosilica is contained in an amount of 5 to 23% by weight based on the solid content of the polyamic acid, A polyimide varnish, wherein the nanosilica has a moisture content of less than 0.5% by weight.

2. 2. The polyimide varnish according to claim 1, wherein the nanosilica is an organosilane surface-modified nanosilica.

3. The organic silane of the nanosilica surface-modified with an organic silane is methyltrimethoxysilane, hexamethyldisiloxane, n-octyltrimethoxysilane, n-octyltriethoxysilane, isooctyltrimethoxysilane, dodecyltrimethoxysilane, octadecyltrimethoxysilane, propyltrimethoxysilane, hexyltrimethoxysilane, 3-methacryloxypropyltrimethoxysilane, 3-acryloxypropyltrimethoxysilane, 3-(methacryloxy)propyltriethoxysilane, 3-(methacryloxy)propylmethyldimethoxysilane, 3-(acryloxypropyl)methyldimethoxysilane, 3-(methacryloxy)propyl Pyldimethylethoxysilane, styrylethyltrimethoxysilane, phenyltriethoxysilane, p-tolyltriethoxysilane, vinylmethyldiacetoxysilane, vinyldimethylethoxysilane, vinylmethyldiethoxysilane, vinyltrimethoxysilane, vinyltriethoxysilane, vinyltriacetoxysilane, vinyltriisopropoxysilane, vinyltriphenoxysilane, vinyltri-t-butoxysilane, vinyltris(isobutoxy)silane, vinyltriisopropenoxysilane, vinyltris(2-methoxyethoxy)silane, diisopropylethylamine phenyltrimethoxysilane (N,N-Diisopropylethylamine 3. The polyimide varnish according to claim 2, comprising at least one selected from the group consisting of N-phenyl-3-aminopropyltrimethoxysilane (PAPTES), N-phenyl-3-aminopropyltrimethoxysilane (N- ...

4. 2. The polyimide varnish according to claim 1, wherein the nanosilica has an average particle size of 1 to 200 nm.

5. 2. The polyimide varnish according to claim 1, wherein the solids content of the polyamic acid is 10 to 50% by weight.

6. 2. The polyimide varnish according to claim 1, wherein the polyamic acid contains a dianhydride monomer and a diamine monomer as polymerized units.

7. The dianhydride monomer is selected from the group consisting of pyromellitic dianhydride (PMDA), biphenyl tetracarboxylic dianhydride (BPDA), benzophenone tetracarboxylic dianhydride (BTDA), oxydiphthalic dianhydride (ODPA), diphenylsulfone-3,4,3',4'-tetracarboxylic dianhydride (DSDA), bis(3,4-dicarboxyphenyl)sulfide dianhydride, 2,2-bis(3,4-dicarboxyphenyl)-1,1,1,3,3,3-hexafluoropropane dianhydride, 2,3,3',4'-benzophenone tetracarboxylic dianhydride, bis(3,4-dicarboxyphenyl)methane dianhydride, 2,2-bis(3,4-dicarboxyphenyl)propane dianhydride, p-phenylene bis(trimeritic monoester acid anhydride), p-biphenylene bis (trimeritic monoester acid anhydride), m-terphenyl-3,4,3',4'-tetracarboxylic dianhydride, p-terphenyl-3,4,3',4'-tetracarboxylic dianhydride, 1,3-bis(3,4-dicarboxyphenoxy)benzene dianhydride, 1,4-bis(3,4-dicarboxyphenoxy)benzene dianhydride, 1,4-bis(3,4-dicarboxyphenoxy)bis 7. The polyimide varnish according to claim 6, comprising at least one member selected from the group consisting of phenyl dianhydride, 2,2-bis[(3,4-dicarboxyphenoxy)phenyl]propane dianhydride (BPADA), 2,3,6,7-naphthalenetetracarboxylic dianhydride, 1,4,5,8-naphthalenetetracarboxylic dianhydride, and 4,4'-(2,2-hexafluoroisopropylidene)diphthalic dianhydride.

8. The diamine monomer is selected from the group consisting of 1,4-diaminobenzene (PPD), 4,4'-diaminodiphenyl ether (ODA), 2,2-bisaminophenoxyphenylpropane (BAPP), metaphenylenediamine, 3,3'-dimethylbenzidine, 2,2'-dimethylbenzidine, 2,4-diaminotoluene, 2,6-diaminotoluene, 3,5-diaminobenzoic acid (DABA), 3,3'-dimethyl-4,4'-diaminobiphenyl, 2,2'-dimethyl-4,4'-diaminobiphenyl (m-tolidine), 2,2'-bis(trifluoromethyl) 3,3'-diaminodiphenyl, 3,3'-dimethyl-4,4'-diaminodiphenylmethane, 3,3'-dicarboxy-4,4'-diaminodiphenylmethane, 3,3',5,5'-tetramethyl-4,4'-diaminodiphenylmethane, 4,4'-diaminobenzanilide, 3,3'-dimethoxybenzidine, 2,2'-dimethoxybenzidine, 3,3'-diaminodiphenyl ether, 3,4'-diaminodiphenyl ether, 3,3'-diaminodiphenyl sulfide, 3,4'-diaminodiphenyl sulfide, 4,4'-diamino diaminodiphenyl sulfide, 3,3'-diaminodiphenyl sulfone, 3,4'-diaminodiphenyl sulfone, 4,4'-diaminodiphenyl sulfone, 3,3'-diaminobenzophenone, 4,4'-diaminobenzophenone, 3,3'-diamino-4,4'-dichlorobenzophenone, 3,3'-diamino-4,4'-dimethoxybenzophenone, 3,3'-diaminodiphenylmethane, 3,4'-diaminodiphenylmethane, 4,4'-diaminodiphenylmethane, 2,2-bis(3-aminophenyl)propane, 2,2-bis(4-amino phenyl)propane, 2,2-bis(3-aminophenyl)-1,1,1,3,3,3-hexafluoropropane, 2,2-bis(4-aminophenyl)-1,1,1,3,3,3-hexafluoropropane, 3,3'-diaminodiphenyl sulfoxide, 3,4'-diaminodiphenyl sulfoxide, 4,4'-diaminodiphenyl sulfoxide, 1,3-bis(3-aminophenyl)benzene, 1,3-bis(4-aminophenyl)benzene, 1,4-bis(3-aminophenyl)benzene, 1,4-bis(4-aminophenyl)benzene, 1,3-bis(4-aminophenoxy)benzene (TPE-R), 1,4-bis(3-aminophenoxy)benzene (TPE-Q), 1,3-bis(3-aminophenoxy)-4-trifluoromethylbenzene, 3,3'-diamino-4-(4-phenyl)phenoxybenzophenone, 3,3'-diamino-4,4'-di(4-phenylphenoxy)benzophenone, 1,3-bis(3-aminophenylsulfide)benzene, 1,3-bis(4-aminophenylsulfide)benzene, 1,4-bis(4-aminophenylsulfide)benzene, 1,3 -bis(3-aminophenylsulfone)benzene, 1,3-bis(4-aminophenylsulfone)benzene, 1,4-bis(4-aminophenylsulfone)benzene, 1,3-bis[2-(4-aminophenyl)isopropyl]benzene, 1,4-bis[2-(3-aminophenyl)isopropyl]benzene, 1,4-bis[2-(4-aminophenyl)isopropyl]benzene, 3,3'-bis(3-aminophenoxy)biphenyl, 3,3'-bis(4-aminophenoxy)biphenyl, 4,4'-bis(3-aminophenoxy)biphenyl, 4,4'-bis(4-aminophenoxy)biphenyl, bis[3-(3-aminophenoxy)phenyl]ether, bis[3-(4-aminophenoxy)phenyl]ether, bis[4-(3-aminophenoxy)phenyl]ether, bis[4-(4-aminophenoxy)phenyl]ether, bis[3-(3-aminophenoxy)phenyl]ketone, bis[3-(4-aminophenoxy)phenyl]ketone, bis[4-(3-aminophenoxy)phenyl]ketone, bis[4-(4-aminophen bis[3-(3-aminophenoxy)phenyl]sulfide, bis[3-(4-aminophenoxy)phenyl]sulfide, bis[4-(3-aminophenoxy)phenyl]sulfide, bis[4-(4-aminophenoxy)phenyl]sulfide, bis[3-(3-aminophenoxy)phenyl]sulfone, bis[3-(4-aminophenoxy)phenyl]sulfone, bis[4-(3-aminophenoxy)phenyl]sulfone, bis[4-(4-aminophenoxy)phenyl]sulfone 2,2-bis[3-(3-aminophenoxy)phenyl]propane, 2,2-bis[3-(4-aminophenoxy)phenyl]propane, 2,2-bis[4-(3-aminophenoxy)phenyl]propane, 2,2-bis[3-(3-aminophenoxy)phenyl]sulfone, bis[3-(3-aminophenoxy)phenyl]methane, bis[3-(4-aminophenoxy)phenyl]methane, bis[4-(4-aminophenoxy)phenyl]methane, 2,2-bis[3-(3-aminophenoxy)phenyl]propane, The polyimide varnish according to claim 6, which contains one or more selected from the group consisting of 2,2-bis[3-(4-aminophenoxy)phenyl]-1,1,1,3,3,3-hexafluoropropane, 2,2-bis[4-(3-aminophenoxy)phenyl]-1,1,1,3,3,3-hexafluoropropane, 2,2-bis[4-(4-aminophenoxy)phenyl]-1,1,1,3,3,3-hexafluoropropane, and 2,2-bis[4-(4-aminophenoxy)phenyl]-1,1,1,3,3,3-hexafluoropropane.

9. 2. The polyimide varnish according to claim 1, wherein the polyamic acid contains pyromellitic dianhydride (PMDA) and 4,4'-diaminodiphenyl ether (ODA) as polymerized units.

10. The polyimide varnish further comprises an organic solvent, The polyimide varnish according to claim 1, wherein the organic solvent comprises at least one selected from the group consisting of N-methyl-pyrrolidone (NMP), N,N'-dimethylformamide (DMF), N,N'-diethylformamide (DEF), N,N'-dimethylacetamide (DMAc), dimethylpropanamide (DMPA), N,N-diethylacetamide (DEAc), dimethylsulfoxide (DMSO), 3-methoxy-N,N-dimethylpropanamide (KJCMPA), p-chlorophenol, o-chlorophenol, γ-butyrolactone (GBL), diglyme, and naphthalene.

11. The polyimide varnish according to claim 1 , wherein the polyimide varnish has a haze of 1.5% or less.

12. A polyimide cured product obtained by curing the polyimide varnish according to any one of claims 1 to 11.

13. The cured polyimide according to claim 12, wherein the cured polyimide has a haze of 1.5% or less.

14. The polyimide cured material according to claim 12, wherein the voltage endurance characteristic, which is the time that an insulating material can withstand a predetermined voltage according to IEC-60851-5, is 300 minutes or more.

15. A polyimide coating comprising the polyimide varnish according to any one of claims 1 to 11.

16. An electric wire comprising the polyimide coating of claim 15.

Citation Information

Patent Citations

  • Ketone solvent dispersion silica sol and resin composition

    WO2020230823A1

  • Aluminum-containing silica sol dispersed in nitrogen-containing solvent, and resin composition

    WO2022097694A1

  • Polyamic acid composition and method for preparing same

    WO2023075411A1

  • Polyamic acid composition and method for preparing same

    WO2023075413A1